2019
DOI: 10.1080/2162402x.2019.1574198
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles expressing adenosinergic ectoenzymes and their potential role in modulating bone marrow infiltration by neuroblastoma cells

Abstract: Metastatic diffusion of Neuroblastoma (NB) cells in the bone marrow (BM) represents the most negative prognostic factors for NB patients. Multiple immune escape mechanisms are postulated as responsible. Our working hypothesis is that adenosine (ADO), an immunosuppressive molecule along with the ectoenzymatic pathways (CD39-CD73 and CD38-CD203a/PC-1-CD73) controlling its production, are involved in the dynamics of NB cells in the BM. The results indicate that ectonucleotidases are expressed by i) NB cell lines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Similar results were obtained analyzing EVs from NB patients [71]. Constitutive high levels of CD38, CD203a, CD39 and CD73 expression have been described (superior to those from healthy controls) in terms of (i) percentage of positive EVs, and (ii) levels of expression, witnessed by a higher fluorescence intensity.…”
Section: Cd38 Expression On Extracellular Vesicles: Another Mechanismsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar results were obtained analyzing EVs from NB patients [71]. Constitutive high levels of CD38, CD203a, CD39 and CD73 expression have been described (superior to those from healthy controls) in terms of (i) percentage of positive EVs, and (ii) levels of expression, witnessed by a higher fluorescence intensity.…”
Section: Cd38 Expression On Extracellular Vesicles: Another Mechanismsupporting
confidence: 78%
“…Interestingly, our study also described as CD38 + and CD73 + EVs in the BM negatively affected the event-free survival of NB patients, confirming their critical impact on the immune-privileged microenvironment of neoplastic cells, that, in turn, support the metastatic spread of NB cells [71].…”
Section: Cd38 Expression On Extracellular Vesicles: Another Mechanismsupporting
confidence: 75%
See 1 more Smart Citation
“…92 Various tumor cell types have been reported to generate CD39 + EVs, including ovarian cancer, prostate cancer, multiple myeloma, neuroblastoma, and head and neck cancer. [92][93][94][95] More recently, it was shown that B cells also produce high levels of EVs expressing CD39 and CD73, which significantly suppress antitumor immunity, particularly in response to chemotherapy. Notably, administration of B cell-derived EVs abrogated chemotherapymediated tumor-specific CD8 + T cells increase in mice, which was prevented by pretreatment of EVs with a CD39 inhibitor (POM-1) or a CD73 inhibitor (APCP).…”
Section: Cd39 and Immunosuppression Through Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Among other surface molecules, microvesicles express integrins, selectins, CD40 or CD81, and are involved in intercellular communications, being captured by target cells through endocytosis, receptor-mediated endocytosis or fusion with the plasma membrane [38,39]. We have previously described that EVs released by tumor cells may carry some immunomodulatory molecules (i.e., adenosinergic ectoenzymes), contributing to the inhibition of the host antitumor immune response [40,41]. Moreover, several studies reported the role of HLA-G-bearing EV in modulation of an immune response in normal pregnancy or neoplastic context [42].…”
Section: Introductionmentioning
confidence: 99%